The effects of the avilamycin, Protexin® and basil essential oil supplements on ileal bacteria of broiler chickens (Veterinary Science Development, 2015)
The effects of probiotic (Protexin®, Protexin Veterinary, Somerset, UK), medicinal plant (basil essential oil) and an antibiotic growth promoter (avilamycin) as broiler feed additives on ileal bacteria of broilers were studied. A total of 600 Arian broilers were divided into 6 treatments, with 4 replicates of 25 birds. Treatments were a plant essential oil in 3 level (200, 400 and 600 ppm), the probiotic (150 ppm), an antibiotic (150 ppm) and a control group with no additives. Birds in different treatments received the same diets during the experimental period. The results showed that probiotic treatment significantly decreased total bacteria counts (P0.05). The lowest and highest lactic acid bacteria in ileum were obtained by the control group and in birds receiving 400 ppm basil essential oil, respectively. Moreover, addition of 600 ppm of basil essential oil into diet decreased the number of E.coli colonies as compared to other treatments (P